A SIMPLE METHOD FOR ESTIMATION OF FLUX LINKAGES OF AN ASYNCHRONOUS MOTOR - Dushinova, E. V.; Levykina, V. I.; Vasilyeva, E. V. (Radio Electronics, Computer Science, Control, 2024)
New algorithm for flux estimations, corresponding they synchronous speeds and modules, which able to work on the all frequency was developed. Proposing integrator of two faze signals is the simple with respect to calculation and provide high precision of showing variable estimation.